Energy efficiency analysis: A household digital transformation - Lima, Gunnar [UNESP]; Nascimento, Andreas [UNESP]; Oliveira, Marcelo P. [UNESP]; Dias, Fagner L. G. (American Institute of Mathematical Sciences (AIMS), 2024)
Nowadays, the increased demand for energy and electrification associated with higher production costs from renewable and cleaner sources has driven up prices, impacting the industrial, commercial, and residential sectors. With a direct influence on the development of these economic sectors, its direct and indirect impacts to products and services have become important to find more efficient ways and best practices on energy use to support sustainable development. Aiming to shed light on this topic, and how individuals and society behave in this energy market transformation, this article explores opportunities for reducing electricity consumption through the use of modern technologies, such as of monitoring, optimization, automation, and adjustment of routines. At the same time, it is also our intention to bring to the surface a discussion around the rational use of everyday resources and raising the awareness of its impact to individuals and institutions. At its core, this work consists of continuous data collection of single devices and equipment in regard to status, energy consumption, and other relevant data of a typical household. Through behavioral changes and introduction of smart home automation techniques, it was possible to trace a parallel comparison between different scenarios and their influence on the energy consumption without negative impact to the comfort of individuals. Seeking a continuous improvement approach, extensive iterations were conducted, and it was possible to notice not only an energy efficiency improvement, but at the same time gains in living standards and safety. The significant results observed over subsequent months and years highlight not only practical and financial benefits, but also increased awareness and behavioral changes toward the rational use of electricity in households.
Keywords: energy efficiency; energy optimization; home automation; internet of things; IoT; smart home